2010
DOI: 10.5194/dwes-3-63-2010
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence spectroscopy as a tool for determination of organic matter removal efficiency at water treatment works

Abstract: Abstract. Organic matter (OM) in drinking water treatment is a common impediment responsible for increased coagulant and disinfectant dosages, formation of carcinogenic disinfection-by products, and microbial re-growth in distribution system. The inherent heterogeneity of OM implies the utilization of advanced analytical techniques for its characterization and assessment of removal efficiency. Here, the application of simple fluorescence excitation-emission technique to OM characterization in drinking water tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 34 publications
3
15
0
Order By: Relevance
“…In Figure 2.5b, coagulation was demonstrated to effectively decrease the fluorescence of all NOM components, with the largest decrease in the fulvic acid-like region (Farré et al 2016a). This is in agreement with other previous studies where DOC removal by coagulation showed linear relationship with the decrease of fluorescence in the humic and fulvic acid regions (Bieroza et al 2010, Gone et al 2009). Lowest fluorescence was observed after ozonation and BAC filtration (Figure 2.5b), suggesting the effectiveness of oxidation in transforming aromatic compounds.…”
Section: Fluorescence Spectroscopysupporting
confidence: 94%
See 1 more Smart Citation
“…In Figure 2.5b, coagulation was demonstrated to effectively decrease the fluorescence of all NOM components, with the largest decrease in the fulvic acid-like region (Farré et al 2016a). This is in agreement with other previous studies where DOC removal by coagulation showed linear relationship with the decrease of fluorescence in the humic and fulvic acid regions (Bieroza et al 2010, Gone et al 2009). Lowest fluorescence was observed after ozonation and BAC filtration (Figure 2.5b), suggesting the effectiveness of oxidation in transforming aromatic compounds.…”
Section: Fluorescence Spectroscopysupporting
confidence: 94%
“…Compared to absorbance, fluorescence spectroscopy is a more sensitive and selective characterization method. This technique has evolved from measurements of simple selected excitation or emission wavelengths to simultaneous collection of fluorescence measurements in a wide range of excitation and emission wavelengths (Bieroza et al 2010). It is widely applied to get spectral signatures or optical maps of water samples through a three-dimensional plot of excitation energy, emission wavelength and fluorescence intensity, known as excitation-emission matrix (EEM) (Chen et al 2003, Hudson et al 2007, Markechova et al 2013).…”
Section: Fluorescence Spectroscopymentioning
confidence: 99%
“…The research applications of aquatic fluorescence tracking have also been extended to include drinking water sources [68]. Several fluorescence studies have recently been undertaken to investigate the performance of drinking water treatment processes and have been able to successfully detect membrane fouling events [109,110] as well as to quantify organic matter removal and efficiency [111][112][113][114]. This area has also seen the early development of a deep-UV LED and laser-induced fluorescence system for fluorescence detection of water-dissolved organic species, looking toward the real-time fluorescence monitoring of drinking water [115].…”
Section: Identification Of Contamination Using Fluorescence Fingerprimentioning
confidence: 99%
“…The fluorescence intensity is linear proportion to the humic acid concentration [2]. Fluorescent technology is often used to measure the concentration of humic acid in natural waters [3][4][5]. The carboxyl and phenolic functional groups of humic acid contains hydroxyl bonds, which are the main bonding position with the metal ions.…”
Section: Introductionmentioning
confidence: 99%